A Book Interaction Scheme to Enhance Children’s Reading Experiences and Preferences - Zhang, Mingming; Hou, Guanhua; Chen, Yeh-Cheng; Zhang, Tao; Yang, Jie (Frontiers in Psychology, 2020)
Human needs motivate the improvement of book interaction scheme. The interaction between children and book is an essential part of the children’s reading experience. Publishers are working very hard to cultivate children’s reading habits and attract their attention to traditional books all over the world. Considering the invaluable reading experience and preference residing in the social network and big data content, at present, deep learning have been used in many areas and presents good performance in predication ability. This paper aimed to investigate the effect of book interaction design on 5-6 years old children’s reading affective experience and preference by measuring reading time, emotion and preferences, so as to improve their reading experience and design properly interaction of books for them. The result showed that preschool children (5-6 years old) prefer sensory interaction the most, and book interaction design has significant influence on reading time, affective experience and subjective ratings. Girls around 5-6 years preferred folding interaction and pop-up interaction in reading. These results summarized as practical guidelines are suit for book publishers to design better books for children.